KETAHANAN PANGAN PETANI PADI SAWAH: SEBUAH PENELITIAN TERAPAN UNTUK MENEMUKAN MODEL GARIS KETAHANAN PANGAN DI SULAWESI UTARA - Elsje Pauline Manginsela; Oktavianus ., Porajouw; Benny Adrian Berthy Sagay (Sam Ratulangi University, 2018)
This study aims to: calculate the amount of rice consumption per capita per year of rice farmers; to increase knowledge about when lowland rice farmers experience a shortage of rice and cannot afford rice because there is no purchasing power what they do to overcome it?; to measure the level of food security and the ratio of fear to the families of lowland rice farmers. This research was conducted from July to November 2018 in Mopait Village and Pangian Village. which is one of the rice-producing villages in Bolaang Mongondow Regency, North Sulawesi. This research used quantitative and qualitative data collection methods concerning the production, fulfillment of rice consumption and the sale and purchase of rice at the level of the rice paddy farmer family. Interviews were conducted with farmers and village leaders as primary data sources. While the secondary data sources came from the Central Sulawesi Statistics and Agriculture Office of North Sulawesi. Data analysis uses quantitative and qualitative data analysis approaches. Quantitative and Qualitative Modeling of Food Security Lines and Farmer Fear Ratio. By using this Food Resilience Line Model, it will be known whether the Family Food Security of Paddy Farmers is strong or weak. Calculation of Farmer's Fear Ratio to find out whether farmers are pessimistic or optimistic about fulfilling rice consumption needs. The results showed that the amount of rice consumption per capita per year for paddy rice farmers, in Mopait Village rice consumption was 121 rice per capita per year. Whereas rice farmers in Pangian Village consume rice with 185 kg of rice per capita per year. At a time when lowland rice farmers lack rice and cannot afford to buy it at the market, they will borrow rice from the mill. The line of food security in the two research villages shows different figures in Mopait Village >1 while in Pangian Village <1. This means that the level of food security in paddy rice farming families in Mopait Village is higher than Pangian Village. While the paddy rice farmers in Mopait Village this year felt less fear compared to 5 years ago but for the next 5 years they remain more pessimistic than this year. Rice farmers in Pangian are more optimistic.